2019
DOI: 10.3390/land8020032
|View full text |Cite
|
Sign up to set email alerts
|

Net Global Warming Potential of Spring Wheat Cropping Systems in a Semiarid Region

Abstract: Investigations of global warming potential (GWP) of semiarid cropping systems are needed to ascertain agriculture’s contributions to climate regulation services. This study sought to determine net GWP for three semiarid cropping systems under no-tillage management in the northern Great Plains of North America: spring wheat (Triticum aestivum L.)—fallow (SW-F), continuous spring wheat (CSW) and spring wheat—safflower (Carthamus tinctorius L.)—rye (Secale cereale L.) (SW-S-R). Management records, coupled with pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…(Archer et al, 2020; Halvorson et al, 2016, 2019; Liebig et al, 2019; Liebig, Archer, & Tanaka, 2014; Nouwakpo et al, 2019; Reeves et al, 2014; Sanderson et al, 2015)…”
Section: Overviewunclassified
See 1 more Smart Citation
“…(Archer et al, 2020; Halvorson et al, 2016, 2019; Liebig et al, 2019; Liebig, Archer, & Tanaka, 2014; Nouwakpo et al, 2019; Reeves et al, 2014; Sanderson et al, 2015)…”
Section: Overviewunclassified
“…• Impacts of conservation practices on crop, forage, and livestock production and economics • Soil characteristics, greenhouse gas flux, water use • Within field water quality measured through using rainfall simulation (Archer et al, 2020;Halvorson et al, 2016Halvorson et al, , 2019Liebig et al, 2019;Nouwakpo et al, 2019;Reeves et al, 2014;Sanderson et al, 2015) Platte River/High Plains Aquifer -X 1,3,4 (Garbrecht & Starks, 2009;Moriasi et al, 2018;Schoof et al, 1987;Van Liew et al, 2003) Texas Gulf Harmel et al ( 2014) X X 1,3 4…”
Section: Overviewmentioning
confidence: 99%
“…Groups with associated soil attributes (in parentheses) were water cycling (porosity, sorptivity, and water‐holding capacity), soil structural maintenance (water stable aggregation and VESS), nutrient supply potential (soil pH, N mineralization, and cation exchange capacity), nutrient cycling potential (urease, phosphatase, and β‐glucosidase activities), biological habitat (FAME components of total biomass, bacteria, and fungi), and climate regulation (soil NO 3 –N, WFPS, and soil organic C). Metrics for climate regulation were adapted from Liebig and Varvel (2003) and were framed by previous NGPRL studies where “hot moments” of N 2 O flux occurred prior to crop seeding when soil conditions were wet and available N was abundant (Liebig et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The positive, though significantly lower net GWP for ungrazed cropland corresponded with other studies of semiarid cropping systems (116-1948 kg CO 2equiv. ha -1 yr -1 ; Liebig et al 2019;Tellez-Rio et al 2017), though a study on a similar soil type in northeast Montana found rainfed cropping systems to have negative net GWP (-292 to -2107 kg CO 2equiv. ha -1 yr -1 ; Sainju et al 2014).…”
Section: System Effects On Net Gwp and Ghgimentioning
confidence: 99%
“…Concentration of N 2 O and CH 4 inside each vial was measured by gas chromatography using a Varian Model 3800 and Combi-Pal auto-sampler. Description of the gas chromatograph, calibration protocols, and flux rate calculations are described elsewhere (Liebig et al 2019;Phillips et al 2009).…”
Section: Soil Carbon Measurementsmentioning
confidence: 99%